IMPLEMENTATION METHOD OF MASTER SLAVE SYSTEM FOR MOTORCYCLE AND SAFETY HELMETS - Nova Suryangga (JAREE (Journal on Advanced Research in Electrical Engineering), 2018)
Abstract— Motorcycle theft often occurs due to many factors other than the theft of a motorcycle helmet is now rampant theft occurs, in this study the authors focus the security both of these by using the communication system master slave on a bike motorcycle and helmet so it can trigger an alarm when a helmet or motorcycles stolen and for additional security features were added to the tracking using the GPS module and GPS tracker bravo so give extra safeguards on the motorcycle and helmet .Keywords: Master slave; GPS; The alarm; Motorcycles; Helmet.